(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Any external physical, chemical, biological impact on the organism leads to changes in the structure and function of the organs of this organism. In this case, the body responds by changing the clinical and laboratory parameters, including the morphology of organs, within the framework of compensatory-adaptive mechanisms [1, 14]. In this article, the morphometric parameters of the testicles of rats of different ages that received radiation were examined. It has been proven in the experiment that the radiation, which has a negative effect on the morphological structures of the testicle, has a significant effect on all the morphometric indicators of this organ. Chronic radiation sickness affects the vasculature of the testes and convoluted tubules, where the diameter of arterioles and venules, as well as the diameter of the convoluted tubules, is further reduced by radiation.